Psychoeducational Groups Based on Dasa Pitutur from Sunan Kalijaga: An Indigenous Counseling to Enhance Other Group Orientation - Mulawarman, Mulawarman; Amin, Zakki Nurul; Muslikah, Muslikah; Hariyadi, Sigit; Kurniawan, Kusnarto (Jurnal Kajian Bimbingan dan Konseling, 2021)
Some Western counseling approaches are not applicable in local cultures. Consequently, counselors have to accommodate the local culture to improve the efficacy of their services. This research aims to formulate indigenous counseling based on the Javanese culture of Dasa Pitutur from Sunan Kalijaga. Using that culture, the counselors are expected to improve the participants’ cultural skills and respect for other cultures. It used the hermeneutic method with discourse analysis to interpret the messages’ structure and pragmatic. The analysis result signifies that the Dasa Pitutur values are relevant with the other group orientation. The primary message taught in Dasa Pitutur is encouraging humans to comprehend their life journey and position to willingly and voluntarily accept their obligations and nature. Linear to their position as a social creature, they have to be aware of the essential values from their relationship, dependency, and appreciation toward other humans. This study can be an enrichment material of cultural values-based guidance and counseling science.